Analisis Pengaruh Islamic Corporate Governance (ICG) Dan Intellectual Capital (IC) Terhadap Maqashid Syariah Indeks (MSI) Pada Perbankan Syariah Di Indonesia - Nono Hartono (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2018)
As an institution based on sharia principles (Islamic banks) certainly has differented characteristics from other companies in its performance orientation. Islamic banking is required to work in accordance with sharia business principles and ethics, one of which is through the implementation of governance (Islamic Corporate Governance/ICG) and the utilization of capital capital (Intellectual Capital/IC) in order to achieve the objectives of establishing Islamic banks in accordance with Islamic maqashid (measured through Maqashid Syariah Index/MSI). The objectives are (1) find out and analyze the effect of Islamic Corporate Governance (ICG) disclosures to maqashid syariah index (MSI) of Indonesian Islamic banking; and (2) knowing and analyzing the influence of Intellectual Capital (IC) to maqashid syariah index (MSI) of Indonesian Islamic banking. The method used content analysis approach for ICG, the iB-VAIC method for IC and Sekaran method on MSI calculations. The sample of Islamic banks was used 11 Islamic Commercial Banks (BUS) from a population of 13 BUS in the period 2013-2017. The sampling method was used purposive sampling. The results showed that both ICG and iB-VAIC had positive and significant effects on MSI. This means that the disclosure of ICG items and IC management will have an impacted on increasing MSI value of Islamic banks.Â Keywords : Islamic Corporate Governance, Intellectual Capital, Maqashid Syariah Index